(3GdQYGjI aj JLhjO GdbQBfs - (3CHh eMeO ecj Hf CHj WGdH Hf MehT Hf eMeO GdCfOdSj GdbjSj, ecj Hf CHj WGdH,J (B437 (3g` s ((3HjJ GdebOS s)
(3ChdgG (B:s
(3GdMeO ddg GdefYe HBdGFg GdeJaVd HfYeGFg, GdPi de jRd HUaGJg hCSeGFg, GdPi CfRd GdcJGH Ydi YHOg hQShdg eMeO Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Je cJGH GdQYGjI dJLhjO GdbQGAI hJMbjb daX GdJdGhI HYde eNGQL GdMQha hUaGJgG hCdbGHgG hJaSjQ eYGfjgG hJYdjdgG hHjGf GdMQcGJ GdJi JdRegG hPdc HJCjjO Gddg hMSf Jhajbg hYhfg hUdi Gddg Ydi SjOfG eMeO hBdg s
(3Vef eLehY , JQJjHgG (B: 2s
(3bQFJ Ydi NRYd Hf Ydi Hf Ndjd SfI (B595 (3g` HHjJ GdebOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B214s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B908s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs